Pengaruh Perilaku Konsumen dan Loyalitas Konsumen terhadap Keputusan Pembelian Produk melalui Pelayanan Konseling - Vanessa Vicario; Immanuel Edy Suranta Sebayang; Elcy Handayani Pramita (Yayasan Literasi Sains Indonesia, 2025)
Consumer purchasing decisions are not solely influenced by logical considerations, but also by emotional dimensions, personal experiences, and the quality of relationships established between consumers and companies. Stemming from this understanding, this research aims to delve deeper into the impact of consumer behavior and consumer loyalty on purchasing decisions, by introducing a more humanistic approach through the implementation of Human Resource Management (HRM) counseling services. In the context of this study, HRM counseling is defined as a crucial two-way communication bridge, facilitating companies to gain a more comprehensive and personal understanding of each customer's unique needs, concerns, and aspirations. This research adopts a quantitative methodology, involving 100 respondents who are active users of brand X products. The collected data were then analyzed using multiple linear regression to identify the relationships between variables. The analysis consistently shows that both consumer behavior and consumer loyalty have a significant and positive influence on purchasing decisions. Furthermore, a key finding of this study highlights that the integration of the HRM counseling approach provides substantial added value. This approach proves effective in building deep emotional closeness, increasing consumer trust, and proactively fostering long-term attachment between customers and companies. Therefore, the results of this study strongly affirm the imperative of developing empathy-based and relationship-oriented management strategies to achieve sustainable consumer loyalty amidst dynamic and competitive market conditions.